2017
DOI: 10.1080/00224499.2017.1394960
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Sex-Liking and Sex-Failure Associations in Men With Sexual Dysfunction

Abstract: Current models of sexual functioning imply an important role for both automatic and controlled appraisals. Accordingly, it can be hypothesized that erectile dysfunction may be due to the automatic activation of negative appraisals at the prospect of sexual intercourse. However, previous research showed that men with sexual dysfunction exhibited relatively strong automatic sex-positive instead of sex-negative associations. This study tested the robustness of this unexpected finding and, additionally, examined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 59 publications
1
10
1
Order By: Relevance
“…In men, better orgasmic functioning was associated with lower levels of implicit liking of erotic stimuli, but implicit sex-wanting associations did not correlate with any aspect of sexual functioning. These starkly contrasting findings, nevertheless, replicated results in previous studies of our research group in female and male patient samples with and without self-and clinician-diagnosed sexual dysfunctions (van Lankveld, Bandell et al, 2018;van Lankveld, de Jong, et al, 2018;van Lankveld et al, 2015), using similar methodology. The present findings in female participants are also similar to those of Dewitte (2015), who investigated a substantially younger sample.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In men, better orgasmic functioning was associated with lower levels of implicit liking of erotic stimuli, but implicit sex-wanting associations did not correlate with any aspect of sexual functioning. These starkly contrasting findings, nevertheless, replicated results in previous studies of our research group in female and male patient samples with and without self-and clinician-diagnosed sexual dysfunctions (van Lankveld, Bandell et al, 2018;van Lankveld, de Jong, et al, 2018;van Lankveld et al, 2015), using similar methodology. The present findings in female participants are also similar to those of Dewitte (2015), who investigated a substantially younger sample.…”
Section: Discussionsupporting
confidence: 87%
“…In a second study among male urological patients with and without sexual problems this finding was replicated, with participants with lower levels of sexual functioning exhibiting a stronger automatic sex-positive association. This effect was largest in the younger age group (van Lankveld et al, 2018). In a nonclinical student sample, several aspects of the sexual behavior of men were predicted best from their implicit sex-liking scores, whereas the sexual behavior of women was best predicted using implicit sex-wanting scores (Dewitte, 2015).…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…Whereas women with and without sexual problem in the present study could be distinguished by their implicit sexual wanting scores, previous studies among men with and without sexual dysfunctions found, in contrast, that implicit liking associations discriminated between both group, while implicit wanting scores in both male groups were equal (van Lankveld et al, 2015(van Lankveld et al, , 2017. Research in which men and women are directly compared is necessary to investigate potential explanations for this gender difference.…”
Section: Discussionmentioning
confidence: 43%
“…This effect was significantly higher in the lower age group. Additionally, an independent negative relationship was found in younger men between explicit sex-liking associations and sexual functioning (van Lankveld et al, 2017).…”
Section: Introductionmentioning
confidence: 95%